Identification of Klebsiella oxytoca by VITEK-2 System in Baghdad Hospitals - Abd Al-Hassan, Rusal E.; Hafidh, Rand R.; Zaman, Muhammad Z. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Klebsiella oxytoca is a Gram-negative rod-shaped bacterium that is becoming resistant to multiple drugs and is frequently endangering patients’ lives. It is a member of the human microbiota. Objectives: To assess the value of identifying K. oxytoca using an automated diagnostic system (VITEK-2) as compared to traditional manual methods. Methods: From July to November 2022, 136 clinical specimens were collected from patients in Baghdad hospitals. The VITEK-2 system was used to recognize the isolated bacteria to the genus and species levels. The biochemical indole test was used as a confirmatory test at the species level. Results: K. oxytoca was more common in urine samples 49 (36.0%), followed by blood samples 21 (15.4%). Of the total collected samples, 77 (56.6%) were from inpatients and 43.3%) were from outpatients. The primary identification by cultural and microscopic examinations diagnosed all the isolates as Klebsiella. The VITEK-2 system recognized them as K. pneumoniae. The indole test confirmed the species as K. oxytoca by the formation of the red ring. Conclusion: Using a simple biochemical test like indole is crucial in clinical laboratories to investigate the accuracy of bacterial identification at the species level. Continuous evaluation of the identification results of the automated systems is needed and can be done by updating the system software for the new emerging pathogens in hospitals.